Utilising cottonseed in animal feeding: A dialectical perspective - Wenjing Wang; Jun Li; Juncheng Liu; Maozhi Ren; Fuguang Li (Modern Agriculture)
Abstract As the population expands livestock industry faces challenges including protein inadequacy and infectious diseases. Natural alternatives can help mitigate these issues, for example, by incorporating plant‐derived metabolites containing appropriate concentrations of natural antibiotics and health‐promoting agents into feed supplements. One promising source is cottonseed, a fat‐ and protein‐rich by‐product of cotton plant (Gossypium spp.). During processing, gossypol, a natural substance with potential adverse effects when consumed long‐term, is often eliminated. However, gossypol has broad‐spectrum antiviral and antimicrobial properties, making it a potential solution to feed safety and animal health concerns. Here, we outline the challenges faced in animal husbandry and discuss how cottonseed may address diverse scenarios.